2007
DOI: 10.1103/physrevlett.99.050601
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions from Saddles of the Potential Energy Landscape

Abstract: The relation between saddle points of the potential of a classical many-particle system and the analyticity properties of its thermodynamic functions is studied. For finite systems, each saddle point is found to cause a nonanalyticity in the Boltzmann entropy, and the functional form of this nonanalytic term is derived. For large systems, the order of the nonanalytic term increases unboundedly, leading to an increasing differentiability of the entropy. Analyzing the contribution of the saddle points to the den… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 13 publications
3
54
0
Order By: Relevance
“…III B that the ground-state QPTs are located at the critical points λ (n) c0 from Eqs. (25) and (27). It turns out that for λ > λ (n) c0 the singularity propagates into the excited spectrum.…”
Section: Excited-state Phase Transitionsmentioning
confidence: 99%
See 3 more Smart Citations
“…III B that the ground-state QPTs are located at the critical points λ (n) c0 from Eqs. (25) and (27). It turns out that for λ > λ (n) c0 the singularity propagates into the excited spectrum.…”
Section: Excited-state Phase Transitionsmentioning
confidence: 99%
“…Such nonanalyticities most commonly follow from the presence of the Hamiltonian stationary points [40,41]. The relation between such points and thermodynamic phase transitions was recently investigated [27] for systems with asymptotically increasing numbers of degrees of freedom. The situation is similar also in the present type of system, described by finite algebraic models, in which the number of degrees of freedom is fixed (independent of the increasing size parameter).…”
Section: Excited-state Phase Transitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…At a stationary point, we have ∇V = 0, the integrand on the righthand side of (1) diverges, and we may expect the stationary point to give an important contribution to the integral. Indeed, it has been shown that, for finite N , every stationary point q s of V induces nonanalytic behavior in s N (v) precisely at the potential energy of the stationary point, v = V (q s )/N [5]. Nonanalyticities of thermodynamic functions are hallmarks of phase transitions.…”
mentioning
confidence: 99%